COBRA methods and metabolic drug targets in cancer. (2nd January 2018) - Apaolaza, Iñigo; José-Eneriz, Edurne San; Agirre, Xabier; Prósper, Felipe; Planes, Francisco J.
ABSTRACT: The identification of therapeutic strategies exploiting the metabolic alterations of malignant cells is a relevant area in cancer research. Here, we discuss a novel computational method, based on the COBRA (COnstraint-Based Reconstruction and Analysis) framework for metabolic networks, to perform this task. Current and future steps are presented.